Journey of the heart the life of Henri Nouwen - Sarandon, Susan, 1946-; Pascal, Karen; Windborne Productions; Vision Video (Firm); Gateway Films (Markham, Ont. ; Worcester, Pa. : Gateway Films : Distributed by Vision Video, 2003)
Biography of Roman Catholic priest and academic Henri Nouwen who abandoned the insular works of academia in favor of a "radical and personal pilgrimage of downward mobility that led him to L'Arche, a community of people with developmental disabilities."
Summary adapted from slipcase.
Writers: Will Finlay, Karen Pascal ; original music, Howard Baer ; director of photography, Gary Elmer ; editors: David Shepherd, Hugo Fava.
Narrator, Susan Sarandon.
DVD format
Keywords: Nouwen, Henri J. M; Spirituality